Gun owners' assessment of gun safety policy: their underlying principles and detailed opinions. - Grene, Kathleen.; Dharani, Amani.; Siegel, Michael. (Tufts University. Tisch Library., 2023)
Keywords: Firearms, Firearm laws, Firearm violence, Gun policy, Guns, Survey study.; Springer Open.